Islam and Competing Nationalisms in the Middle East, 1876-1926 - Soleimani, Kamal (The Modern Muslim World, 2016)
Dedication -- Acknowledgments -- Contents -- List of Abbreviations -- chapter 1: Introduction -- Part I: Religious (Islamic) Thought, Nationalism, and the Politics of Caliphate -- chapter 2: Nationalism and Religious Thought -- Eurocentric Context of the Study of Nationalism -- Secularization, Religion, and Nationalism -- Modern Islamic Political Thought, "Islamism" and Nationalism -- chapter 3: The Politics of the Khilafa, Old and New -- The Emergence of the Caliphate (632) and Ensuing Debates -- Theological Roots of the Late Ottoman Caliphate